State Plan Proposals 1979-80 Volume I Government of West Bengal - Planning Commission (Planning Commission, 1978)
This year the Annual Plan proposals for 1979-80 are being discussed along with the proposals for the Five Year Plan 1978-83. the objectives, strategy and intersectoral priorities of the Annual Plan will, therefore, be determined in the context of the objectives mentioned in the draft Five Year Plan 1978-83 proposals. These objectives include minimum development in the key sectors of power, irrigation, flood control, agriculture, backward areas and the essential social services like health, education, housing and nutrition for the weaker sections. the problem of the seasonal unemployment in the villages still remains a matter of grave concern.
Government of West Bengal, Development and Planning Department